1980
DOI: 10.3109/17453678008990769
|View full text |Cite
|
Sign up to set email alerts
|

Metal Sensitivity in Patients with Metal-To-Plastic Total hip Arthroplasties

Abstract: Out of 134 patients patch tested after total hip replacement (metal-toplastic) 13 were sensitive to one or two of the implanted metals. In a prospective series of 112 patients, nine were sensitive to nickel before and another three developed sensitivity to nickel or cobalt after the arthroplasty. In the retrospective as well as in the prospective series the complications could in all cases but one be explained on grounds other than allergy. The incidence of contact allergy to nickel before a planned arthroplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(45 citation statements)
references
References 13 publications
1
43
0
1
Order By: Relevance
“…Most patients tolerate orthopedic metal implants well; however, complications resulting from immune reactivity to metals have been well documented. [1][2][3][4][5][6] Dermal hypersensitivity to metal is common, with up to 20% of Caucasians being sensitive to nickel. 7 Immune reactions to dermal contact and ingestion of metals, manifested as skin conditions such as eczema, urticaria, erythema, and pruritis, are believed to be of a type IV cell-mediated hypersensitivity.…”
mentioning
confidence: 99%
“…Most patients tolerate orthopedic metal implants well; however, complications resulting from immune reactivity to metals have been well documented. [1][2][3][4][5][6] Dermal hypersensitivity to metal is common, with up to 20% of Caucasians being sensitive to nickel. 7 Immune reactions to dermal contact and ingestion of metals, manifested as skin conditions such as eczema, urticaria, erythema, and pruritis, are believed to be of a type IV cell-mediated hypersensitivity.…”
mentioning
confidence: 99%
“…The number of prospective studies is limited and the results differ. For example: in one examination it was shown that only 3 out of 112 (2.7%) patients with metal-to-metal total hip arthroplasties were allergic to metals [16]. In other studies, 5 out of 72 (6.9%) patients developed allergic reactions to at least one or more metals that were included in the orthopedic not to contain allergenic metals to which the patients were sensitized.…”
Section: Discussionmentioning
confidence: 99%
“…When this degradative process is severe enough it can damage the structural integrity of the implant, and corrosion products are potentially toxic. 1,[5][6][7]9,14,16,18,24,33,37,46,49,50,56,57,[59][60][61][62][63][64]70 Disc replacement designs incorporate cobalt-chromium-molybdenum alloy endplates that are externally coated with titanium for bone ingrowth. The metallic endplates are fixed to polymeric cores and motion takes place between articulating polymer surfaces.…”
Section: Biomaterials Used In Joint Replacementmentioning
confidence: 99%